The Influence of School Environment Conditions, Teacher Professional Competency, and Learning Facilities on IPS Learning Interests in State SD Students in Kecamatan Sambungmacan - Maya Yulita Supriehhatin; Sarwanto Sarwanto; Ajat Sudrajat (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2022)
The results of the observations show that in the learning process in the Elementary School of Connectmacan District, there are still many fifth grade students who are not enthusiastic about participating in learning, this shows that the students' interest in learning social studies is low. This study aims to analyze the influence of the conditions of the learning environment, teacher professional competence, and learning facilities on the students' interest in social studies learning at SDN Connectmacan District. This study uses a quantitative design with an emphasis on explanation (explanatory research). The population of all students in grade V SD Negeri in the Asri Cluster, Kontakmacan District, Academic Year 2019/2020, totaling 8 SD. The sample was taken 4 SDN with simple random sampling technique. Data collection in the form of questionnaires and documentation. The questionnaire instrument was first tested for validity and reliability on students other than respondents. The data analysis technique used the Multiple Linear Regression test. The results showed that there was a positive and significant influence on the condition of the school environment on interest in learning social studies. There is a positive and significant effect of teacher professional competence on interest in learning social studies. There is a positive and significant influence of learning facilities on interest in social studies learning. There is a positive and significant influence on the variable school environment conditions, teacher professional competence, and learning facilities simultaneously on interest in learning.